Thinking through the Mothers : Reimagining Women's Biographies - Beizer, Janet L., 1952- (Book collections on Project MUSE., 2009)
"In Thinking through the Mothers, Janet Beizer surveys modern women's biographies and contemplates alternatives to an approach based in lineage and the form of thought that emphasizes the line, the path, hierarchy, unity, resemblance, reflection, and the aesthetic--mimesis that depends on these ideas." "Through close readings of memoirs and fictions about mothers, Beizer explores how biographers of the women who came before rehearse and rewrite relationships to their own mothers biographically as they seek to appropriate the past in a hybrid genre she calls "bio-autography." Beizer seeks an alternative to women's "salvation biography" or "resurrection biography" that might resist nostalgia, be attentive to silence, and reinvent the means to represent the lives of precursors without appropriating traditional models of genealogy."--Jacket